Radically truncated MeCP2 rescues Rett syndrome-like neurological defects - Tillotson, Rebekah (Nature, 2017)
Heterozygous mutations in the X-linked MECP2 gene cause the profound neurological disorder Rett syndrome (RTT)1. MeCP2 protein is an epigenetic reader whose binding to chromatin primarily depends on 5-methylcytosine (mC)2,3. Functionally, MeCP2 has been implicated in several cellular processes based on its reported interaction with >40 binding partners4, including transcriptional co-repressors (e.g. the NCoR/SMRT complex5), transcriptional activators6, RNA7, chromatin remodellers8,9, microRNA-processing proteins10 and splicing factors11. Accordingly, MeCP2 has been cast as a multi-functional hub that integrates diverse processes that are essential in mature neurons12. At odds with the concept of broad functionality, missense mutations that cause RTT are concentrated in two discrete clusters coinciding with interaction sites for partner macromolecules: the Methyl-CpG Binding Domain (MBD)13 and the NCoR/SMRT Interaction Domain (NID)5. Here, we test the hypothesis that the single dominant function of MeCP2 is to physically connect DNA with the NCoR/SMRT complex, by removing almost all amino acid sequences except the MBD and NID. We find that mice expressing truncated MeCP2 lacking both the N- and C-terminal regions (approximately half of the native protein) are phenotypically near-normal; and those expressing a minimal MeCP2 additionally lacking a central domain survive for over one year with only mild symptoms. This minimal protein is able to prevent or reverse neurological symptoms when introduced into MeCP2-deficient mice by genetic activation or virus-mediated delivery to the brain. Thus, despite evolutionary conservation of the entire MeCP2 protein sequence, the DNA and co-repressor binding domains alone are sufficient to avoid RTT-like defects and may therefore have therapeutic utility.